Targeted Engineering of Cyclooctat‐9‐en‐7‐ol Synthase: A Stereospecific Access to Two New Non‐natural Fusicoccane‐Type Diterpenes. Issue 11 (12th August 2013) - Görner, Christian; Häuslein, Ina; Schrepfer, Patrick; Eisenreich, Wolfgang; Brück, Thomas
Abstract The structural diversity of bioactive diterpenes is due to variations in their macrocyclic carbon skeletons. The chemical synthesis of these macrocycles is challenging. However, the bacterial diterpene synthase cyclooctat‐9‐en‐7‐ol synthase (CotB2) generates a complex macrocycle in a single step with geranylgeranyl diphosphate as an aliphatic substrate. This study investigates the catalytic mechanisms of the native and mutant CotB2, with a focus on identifying new carbon macrocycles. The combination of in silico modelling, targeted diterpene cyclase engineering and structural elucidation by using GC–MS, HRMS and NMR analysis resulted in the identification of new terpene olefins. CotB2 mutants produced two new non‐natural fusicoccane‐type macrocycles with potential bioactivities and the monocyclic compound cembrene. The observed product pattern allowed insights into the mechanistic features of CotB2. Applied strategies enable new consolidated synthesis of natural and non‐natural terpenoid bioactives.